2009
DOI: 10.1038/nn.2270
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the glucocorticoid receptor in human brain associates with childhood abuse

Abstract: Maternal care influences hypothalamic-pituitary-adrenal (HPA) function in the rat through epigenetic programming of glucocorticoid receptor expression. In humans, childhood abuse alters HPA stress responses and increases the risk of suicide. We examined epigenetic differences in a neuron-specific glucocorticoid receptor (NR3C1) promoter between postmortem hippocampus obtained from suicide victims with a history of childhood abuse and those from either suicide victims with no childhood abuse or controls. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

107
2,097
5
64

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 3,036 publications
(2,320 citation statements)
references
References 50 publications
107
2,097
5
64
Order By: Relevance
“…These epigenetic modifications occur without sequential variation. Epigenetic control of gene expression is highly responsive to environmental influences such as ELS, especially during developmentally sensitive periods in early life, as has been shown in rodents (Champagne, 2008; Meaney, 2001; Weaver et al, 2004) and humans (McGowan et al, 2009). DNA methylation, i.e., the attachment of methyl groups (CH 3 ) to the 5-carbon position of cytosine, which typically occurs at so-called CpG dinucleotides where a cytosine base is followed by a guanine base, generally results in gene silencing and is the only epigenetic modification of the human OXTR gene studied to date.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 94%
“…These epigenetic modifications occur without sequential variation. Epigenetic control of gene expression is highly responsive to environmental influences such as ELS, especially during developmentally sensitive periods in early life, as has been shown in rodents (Champagne, 2008; Meaney, 2001; Weaver et al, 2004) and humans (McGowan et al, 2009). DNA methylation, i.e., the attachment of methyl groups (CH 3 ) to the 5-carbon position of cytosine, which typically occurs at so-called CpG dinucleotides where a cytosine base is followed by a guanine base, generally results in gene silencing and is the only epigenetic modification of the human OXTR gene studied to date.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 94%
“…In humans, maternal touch and feed are considered also critical regulators of behavioral and stress responses in the offspring , although its importance as an obesity risk factor and the alteration of epigenetic processes have never been analyzed. However, it has been observed that childhood abuse, neglect and loss induce alterations of the epigenetic mechanisms (McGowan et al, 2009). They are major risk factor for developing depressive disorders later in life (Heim and Binder, 2012) and could be related with epigenetic mechanisms and chronic alterations in cortisol secretion in children that could affect body composition and be causative factors of early-onset obesity, metabolic syndrome, and type 2 diabetes (Pervanidou and Chrousos, 2011).…”
Section: Psychological Stressmentioning
confidence: 99%
“…A set of recent studies [94] provides at least correlational evidence for the idea that comparable epigenetic modifications might occur in humans in response to variations in parent-offspring interactions. These studies examined the methylation status of the exon 1 F promoter of the GR gene, which corresponds to the exon 1 7 promoter in the rat [95], in hippocampal samples obtained from victims of suicide or controls (sudden, involuntary death).…”
Section: The Epigenetics Of Phenotypic Plasticitymentioning
confidence: 99%